The Influence of Trust, Perceived Value and Service Quality on Purchase Intention for Metland Cikarang Housing with Customer Satisfaction as a Mediating Variable - Sara Trias Millenia; Munawar Asikin (Economic, Management, Business and Accountancy International Journal, 2025)
This study examines the effects of Trust, Perceived Value, and Service Quality on Purchase Intention for Metland Cikarang housing, with Customer Satisfaction as a mediating variable. Using a quantitative approach, data were collected through an online survey of 110 active leads during March–May 2025 and analyzed using PLS-SEM with SmartPLS. The proposed model suggests that Trust, Perceived Value, and Service Quality have significant positive effects on Customer Satisfaction and Purchase Intention, with Customer Satisfaction mediating these relationships and Trust acting as a foundational antecedent. The findings are expected to provide strategic insights for improving lead conversion by emphasizing brand trust, value communication, and service quality. This study contributes an integrated model highlighting the psychological pathway from trust to purchase intention in the Indonesian residential property market.